The black book of colours - Cottin, Menena (Walker Books, 2010)
A stunning and unforgettable black book... about colour. Our eyes tell us about colour. But what if you are blind? Can you still know colours? Using simple language and beautifully textured art, this book shows you how to 'see' without your eyes. The pages are black, but using your imagination and your senses you can hear, smell, touch and taste colours! Braille letters accompany the illustrations on every page and a full Braille alphabet offers sighted readers help in deciphering the text with their fingers, and sharing an experience usually known by blind readers alone. Winner of the prestigious BolognaRagazzi 'New Horizons' prize in 2007. Our eyes tell us about colour. But what if you are blind? Can you still know colours? Using simple language and textured art, this book shows you how to 'see' without your eyes. It includes the pages that are black, but using your imagination and your senses you can hear, smell, touch and taste colours.